2021
DOI: 10.3389/fpls.2020.526455
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Specificity: RNAi Mechanisms and Strategies to Reduce Off-Target Effects

Abstract: Short interfering RNAs (siRNAs) are processed from long double-stranded RNA (dsRNA), and a guide strand is selected and incorporated into the RNA-induced silencing complex (RISC). Within RISC, a member of the Argonaute protein family directly binds the guide strand and the siRNA guides RISC to fully complementary sites on-target RNAs, which are then sequence-specifically cleaved by the Argonaute protein—a process commonly referred to as RNA interference (RNAi). In animals, endogenous microRNAs (miRNAs) functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 87 publications
0
47
0
Order By: Relevance
“…We have previously reported a similar variation in phenotypic strength after knockdown with multiple RNAi hairpins targeting other RBPs, notably SF1 , Hrb87F , snf , Prp19 , and others ( Kao et al, 2021 ). These results illustrate the experimental importance of testing multiple, independent RNAi constructs to distinguish hypomorphic from null phenotypes, beyond merely addressing off-target effects ( Mohr & Perrimon, 2012 ; Kaya-Çopur & Schnorrer, 2019 ; Neumeier & Meister, 2020 ). Moreover, tuning the level of knockdown can offer insight into regulatory events that are sensitive to RBP activity level.…”
Section: Discussionmentioning
confidence: 80%
“…We have previously reported a similar variation in phenotypic strength after knockdown with multiple RNAi hairpins targeting other RBPs, notably SF1 , Hrb87F , snf , Prp19 , and others ( Kao et al, 2021 ). These results illustrate the experimental importance of testing multiple, independent RNAi constructs to distinguish hypomorphic from null phenotypes, beyond merely addressing off-target effects ( Mohr & Perrimon, 2012 ; Kaya-Çopur & Schnorrer, 2019 ; Neumeier & Meister, 2020 ). Moreover, tuning the level of knockdown can offer insight into regulatory events that are sensitive to RBP activity level.…”
Section: Discussionmentioning
confidence: 80%
“…In coleopterans, an orally delivered long dsRNA (≥200-500 nucleotides) is processed into the cell to yield siRNAs, which ultimately trigger mRNA degradation [66]. The dsRNA fragment size may be reduced to avoid off-target silencing [68,69]. In addition, protection by nanoparticles increased the efficiency of RNAi action in Euchistos heros [66].…”
Section: Dsrna Stability and Efficiencymentioning
confidence: 99%
“…Nonetheless, these nanoparticle-based RNA pesticides must be simple and the required raw materials should be affordable for low-cost production [61,70]. In addition, application dsRNA-based pesticides through either irrigation or foliar spray must be explored [68] to promote their oral uptake by insects via feeding [15].…”
Section: Dsrna Stability and Efficiencymentioning
confidence: 99%
“…Castellanos et al [31] reported that the combined use of RNAi-mediated gene silencing against the Neotropical brown stink bug Euschistus heros (F.) (Hemiptera, Pentatomidae), together with eggs of the parasitoid Telenomus podisi Ashmead (Hymenoptera, Scelionidae), proved to be a feasible approach. In RNAi-mediated pest control, off-target effects need to be analysed before its implemen-tation [32,33]. In a study by Pan et al [28], the effects of dietary RNAi toxicity assay of Diabrotica virgifera virgifera LeConte (Coleoptera, Chrysomelidae) active dsRNA for the gene V-ATPase proved to be detrimental to four non-target ladybird species (Coleoptera, Coccinellidae).…”
Section: Introductionmentioning
confidence: 99%